HEFT, James L. (Edited by). After Vatican II. Trajectories and hermeneutics. Grand Rapids: Eerdmans, 2012. - Coppe Caldeira, Rodrigo (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2013)
RESENHA HEFT, James L. (Edited by). After Vatican II. Trajectories and hermeneutics. Grand Rapids: Eerdmans, 2012.